Evaluation of Hemostasis in Female Dogs with Mammary Carcinoma and the Influence of Clinical Stage and Histopathological Grade - de Oliveira, Jéssica Rodrigues; Camplesi, Annelise Carla; Calazans, Sabryna Gouveia; Santana, Aureo Evangelista; Silva, Priscila; Firmo, Bruna Fernanda; Bizare, Amanda; da Rosa Sobreira, Márcia Ferreira (Acta Scientiae Veterinariae, 2019)
Background: Mammary tumors are frequent in female dogs, and are biologically similar in female dogs and humans. Hemostatic disorders are common in humans with cancer, and the mechanisms that conduct coagulation activation involve tissue and cancer procoagulant factors and inflammatory cytokines. Despite the importance of coagulopathy diagnosis that evaluate hemostasis, veterinarians rarely request such tests in routine clinical oncology. This study aimed to investigate the possible hemostatic abnormalities in female dogs with mammary carcinomas and assess any associations with prognostic factors for mammary cancer in female dogs. Materials, Methods& Results: A total of 62 female dogs were selected for inclusion in this study regardless of age or breed. The control group consisted of 30 healthy dogs, and the carcinoma group consisted of 32 dogs with a histopathological diagnosis of mammary carcinoma that was free of distant metastases and comorbidities that could interfere with the hemostatic system integrity. The dogs with mammary carcinoma were divided into subgroups according to their histological type, histopathological grading, tumor size, and clinical stage of the disease (TNM) to evaluate the relationships between the subgroups and hemostatic parameters (blood platelet counts, prothrombin time [PT], activated partial thromboplastin time [aPTT], and plasma fibrinogen concentration). The hemostatic parameters were significantly higher in the carcinoma group than in the control group (p ≤ 0.05). These findings indicate that there is a strong association between the occurrence of mammary carcinoma and abnormal hemostatic parameters, as well as a strong association between histopathological grade I and normal hemostatic parameters. In addition, when evaluating subgroups, PT and aPTT values were significantly higher in dogs with histopathological grade II and III tumors than in dogs with histopathological grade I tumors. Furthermore, PT and aPTT values were higher in the clinical stage IV subgroup than in the remaining subgroups. Nonetheless, there was no statistical difference in these values among the clinical stage I, III, and IV subgroups. Discussion: Recent studies demonstrated that thrombocytosis is a common finding in dogs with cancer and that the true incidence of thrombocytosis might be underreported. The prolonged PT and aPTT observed in this study were higher than those described in the literature. The abnormalities in PT and aPTT values detected in female dogs with mammary carcinoma in this study might have been affected by the histopathological severity (grades II and III) and clinical disease stage. Hyperfibrinogenemia detected in the healthy control group was the most common hemostatic abnormality. This finding was close to that found in the literature, in which 66.7% of female dogs presented with high fibrinogen values, which was more evident in dogs of clinical disease stages III and IV. The results indicate that 56% of animals presented with at least three hemostatic abnormalities, including the prolongation of PT and aPTT and hyperfibrinogenemia. These abnormalities were related to advanced clinical stages and histopathological grades II and III. Thus, the observed abnormalities can be indicative of a poorer prognosis and survival time of these patients because the previously identified products of coagulation are important for both tumor dissemination and progression.